Peran Konfromitas Teman Sebaya dalam Perilaku Penyalahgunaan Obat Golongan G pada Remaja Kelompok Geng Motor - rahim, firnasrudin (Journal of Health Education and Literacy, 2025)
Conformity is a change in a person's attitude, behavior or belief caused by group pressure or social influence driven by their own desires because everyone else displays this behavior in order to continue to socialize according to existing social norms. the purpose of the study was to determine the impact of peer conformity on changes in drug abuse behavior in groups of adolescent gangs. Materials and methods: The design of this qualitative study is specifically directed at the use of phenomenological methods. One form of peer conformity is when adolescents are involved in gathering activities carried out with their group. Starting from consuming drugs, drinking alcohol, watching illegal motorcycle racing and rolling looking for victims or objects of peer crime. Conformity is a change in a person's attitude, behavior or belief caused by group pressure or social influence driven by their own desires because everyone else displays this behavior in order to continue to socialize according to existing social norms. the purpose of the study was to determine the impact of peer conformity on changes in drug abuse behavior in groups of adolescent gangs. Materials and methods: The design of this qualitative study is specifically directed at the use of phenomenological methods. One form of peer conformity is when adolescents are involved in gathering activities carried out with their group. Starting from consuming drugs, drinking alcohol, watching illegal motorcycle racing and rolling looking for victims or objects of peer crime.